Need Analysis of Physics Laboratory Design to Enhance Student Creativity in Character Education - Saiyidah Mahtari; Syihabuddin Syihabuddin; Agus Setiawan; Mustika Wati (Postgraduate, University of Mataram, 2024)
This study aims to evaluate the effectiveness of physics laboratory design in supporting the development of student creativity and character and identifying needs for improvement in the practicum context. Using a case study approach, the qualitative research method involved in-depth interviews and questionnaires with 100 Physics Education Study Programme students at Lambung Mangkurat University. The results showed that although the pre-lab activities and practicum guides received positive ratings, there were significant challenges in the relevance of the practicum to everyday life, practicum design that supports collaboration, and the development of creativity. Students felt the lab time and guidelines did not support creative and collaborative problem-solving. These findings indicate the need for a more open, problem-based laboratory design and better integration between technical aspects, creativity, and character education. This study recommends the development of laboratory modules that support problem-solving and collaborative approaches to improve students' skills holistically.